Evaluation of the Texas Youth Commission's Chemical Dependency Treatment Program, 1998-1999 - Kelly, William R. ([Verlag nicht ermittelbar], 2003)
This study consists of data from both the process evaluation and the outcome evaluation of the Texas Youth Commission's (TYC) Chemical Dependency Treatment Program (CDTP). The research goal of the first part of the study was to provide a systematic and empirical process evaluation of appropriate program placement and whether and to what extent selected individual-level factors were related to key measures of program progress, as well as to variations in process outcomes across each of five treatment sites. The research goal of the second part of the study was to provide a systematic and empirical outcome evaluation of the impact of the TYC Chemical Dependency Treatment Program, including determination of the extent to which certain risk, need, amenability, program performance and delivery, and aftercare factors affected treatment impact. Data were obtained from the Texas Youth Commission, the state corrections agency responsible for serving violent and serious delinquent youth committed to the custody of the state. TYC collects a range of information on the risk, needs, and treatment amenability of its youths. Also, program performance is measured through the use of an exit assessment conducted by program staff, which essentially provides a report card summarizing each youth's involvement and progress in treatment. Data in this evaluation cover all juveniles who entered the CDTP from January through October 1998, and who were discharged by April 1, 1999. The treatment group consists of youths who invariably had a high need for chemical dependency treatment. The control group consists of youths who were eligible for treatment in the CDTP during this same time period but who did not receive it due to limited CDTP bed space. To obtain measures of drug use/abuse relapse, aftercare participation, and parole performance, a parolee data worksheet was created. TYC was able to provide information on who received chemical dependency treatment while on parole. Five core variables of the process evaluation data are program completion, program expulsion, days to completion, days to expulsion, and number of behavior infractions. The process evaluation includes the following variables from individual exit assessments: the youth's overall participation, whether the youth understood the curriculum, understood addiction, sought help, acknowledged addiction, and acknowledged impact, the youth's performance grade, whether the youth committed to be drug-free, family involvement, special circumstances, and performance index. Demographic variables are race, age, parents' marital status, and gender. Variables addressing risk factors include classifying offense, offender class, risk level, number of felony referrals, number of felony adjudications, number of previous TYC commitments, and number of parole revocations. Other variables in the process evaluation address the Substance Abuse Subtle Screening Inventory (SASSI), the Diagnostic Statistical Manual IV (DSM-IV) chemical dependency treatment need, TYC treatment amenability score, and the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). Variables available in the outcome evaluation data address issues of rearrest, higher custody level, aftercare sessions, drug tests, and parole compliance.